The spectrum of pulmonary amyloidosis - Riehani, Anas; Soubani, Ayman O (Respiratory medicine, 2023)
Amyloidosis is a disease caused by misfolded proteins that deposit in the extracellular matrix as fibrils, resulting in the dysfunction of the involved organ. The lung is a common target of Amyloidosis, but pulmonary amyloidosis is uncommonly diagnosed since it is rarely symptomatic. Diagnosis of pulmonary amyloidosis is usually made in the setting of systemic amyloidosis, however in cases of localized pulmonary disease, surgical or transbronchial tissue biopsy might be indicated. Pulmonary amyloidosis can be present in a variety of discrete entities. Diffuse Alveolar septal amyloidosis is the most common type and is usually associated with systemic AL amyloidosis. Depending on the degree of the interstitial involvement, it may affect alveolar gas exchange and cause respiratory symptoms. Localized pulmonary Amyloidosis can present as Nodular, Cystic or Tracheobronchial Amyloidosis which may cause symptoms of airway obstruction and large airway stenosis. Pleural effusions, mediastinal lymphadenopathy and pulmonary hypertension has also been reported. Treatment of all types of pulmonary amyloidosis depends on the type of precursor protein, organ involvement and distribution of the disease. Most of the cases are asymptomatic and require only close monitoring. Diffuse alveolar septal amyloidosis treatment follows the treatment of underlying systemic amyloidosis. Tracheobronchial amyloidosis is usually treated with bronchoscopic interventions including debulking and stenting or with external beam radiation. Long-term prognosis of pulmonary amyloidosis usually depends on the type of lung involvement and other organ function.Amyloidosis is a disease caused by misfolded proteins that deposit in the extracellular matrix as fibrils, resulting in the dysfunction of the involved organ. The lung is a common target of Amyloidosis, but pulmonary amyloidosis is uncommonly diagnosed since it is rarely symptomatic. Diagnosis of pulmonary amyloidosis is usually made in the setting of systemic amyloidosis, however in cases of localized pulmonary disease, surgical or transbronchial tissue biopsy might be indicated. Pulmonary amyloidosis can be present in a variety of discrete entities. Diffuse Alveolar septal amyloidosis is the most common type and is usually associated with systemic AL amyloidosis. Depending on the degree of the interstitial involvement, it may affect alveolar gas exchange and cause respiratory symptoms. Localized pulmonary Amyloidosis can present as Nodular, Cystic or Tracheobronchial Amyloidosis which may cause symptoms of airway obstruction and large airway stenosis. Pleural effusions, mediastinal lymphadenopathy and pulmonary hypertension has also been reported. Treatment of all types of pulmonary amyloidosis depends on the type of precursor protein, organ involvement and distribution of the disease. Most of the cases are asymptomatic and require only close monitoring. Diffuse alveolar septal amyloidosis treatment follows the treatment of underlying systemic amyloidosis. Tracheobronchial amyloidosis is usually treated with bronchoscopic interventions including debulking and stenting or with external beam radiation. Long-term prognosis of pulmonary amyloidosis usually depends on the type of lung involvement and other organ function.